Feasibility Study of Electric Rubber-Tire Bus Potential in Chiang Mai - Electrification Planning - P. Wirasanti (2018)
© 2018 IEEE. To study feasibility of establishing the electric rubber-tire bus in Chiang Mai, Thailand, the electrification planning is consequently one of the key topics. At first, the backward-facing method is selected for the bus modelling. This method is a quasi-static model, thus, it is no need to deal with the differential equation of motor. The driving cycle and the road incline profile are the input parameter, hence the driving cycle is simulated by PTV vissim program. The transport network, the traffic flow, the distance between bus stops and the cross section are taken into account for simulated driving cycle. The road incline is examined by the elevation difference between two bus stops in the google earth pro. The result of the proposed model is used to study the power profile along the driving distance and the total energy consumption. The interpretation of both information results in power network design. One of the most traffic feeders of the light rail transit system is selected for a case study. As a result, the peak power is 176 kW, and the total energy consumption is 16 kWh for one outbound. The minimum requirements of electrification based on the battery bus and the trolley bus are finally discussed. All in all, this paper demonstrates a complete process of electrification planning of electric bus.